Integrasi dan Adaptasi Sosial Migrant di Korea Selatan (Jurnal Ilmu Kesejahteraan Sosial, 2018)
This research was conducted to find out the empowerment effort done by DKI Jakarta Provincial Government through technical unit namely Unit Pengelola Dana Bergulir (UPDB) as implementing unit of Community Economic Empowerment Program (Program Pemberdayaan Ekonomi Masyarakat Kelurahan) to the administrators/managers of cooperatives or Koperasi Jasa Keuangan Pemberdayaan Ekonomi Masyarakat Kelurahan (KJK PEMK) as partner of UPDB in implementing this program. The research was conducted at KJK PEMK Kelapa Gading Barat, which is KJK PEMK which is considered smoothly in installment refund. The research was conducted using qualitative approach, with descriptive research type, and informant selection technique was done by purposive sampling. Findings of research indicate that there are efforts of empowerment from UPDB to administrators/managers of KJK PEMK, especially in the form of capacity building. It is intended that the administrators/managers KJK PEMK has the ability to manage KJK PEMK.